Abnormalities in neuroendocrine stress response in psychosis: the role of endocannabinoids. Issue 1 (15th September 2015) - Appiah-Kusi, E.; Leyden, E.; Parmar, S.; Mondelli, V.; McGuire, P.; Bhattacharyya, S.
Abstract : The aim of this article is to summarize current evidence regarding alterations in the neuroendocrine stress response system and endocannabinoid system and their relationship in psychotic disorders such as schizophrenia. Exposure to stress is linked to the development of a number of psychiatric disorders including psychosis. However, the precise role of stress in the development of psychosis and the possible mechanisms that might underlie this are not well understood. Recently the cannabinoid hypothesis of schizophrenia has emerged as a potential line of enquiry. Endocannabinoid levels are increased in patients with psychosis compared with healthy volunteers; furthermore, they increase in response to stress, which suggests another potential mechanism for how stress might be a causal factor in the development of psychosis. However, research regarding the links between stress and the endocannabinoid system is in its infancy. Evidence summarized here points to an alteration in the baseline tone and reactivity of the hypothalamic–pituitary–adrenal (HPA) axis as well as in various components of the endocannabinoid system in patients with psychosis. Moreover, the precise nature of the inter-relationship between these two systems is unclear in man, especially their biological relevance in the context of psychosis. Future studies need to simultaneously investigate HPA axis and endocannabinoid alterations both at baseline and following experimental perturbation in healthy individuals and those with psychosis to understand how they interact with each other in health and disease and obtain mechanistic insight as to their relevance to the pathophysiology of schizophrenia.